Use of Eichhornia crassipes dry matter as organic substrate for germination and initial growth of corn - dos Anjos, Mariane Luz; Henares, Matheus Nicolino Peixoto; Bória-Fernandez, Jaqueline Aparecida (Ecosistemas y Recursos Agropecuarios, 2018)
The objective was to evaluate the potential use of the dry matter of the aquatic macrophyte (Eichhornia crassipes) as a substrate for germination and initial growth of corn (Zea mays L.). The experimental design was completely randomized with four treatments and ve replicates. The treatments consisted of testing substrates with different levels of E. crassipes dry matter and agricultural soil mixtures, with 100 % E. crassipes dry matter, 50% E. crassipes dry matter and 50 % agricultural soil, 25 % E. crassipes dry matter and 75% agricultural soil, and 100% commercial agricultural substrate. Average stem height and diameter, and shoot and root fresh and dry mass were compared by one-way ANOVA and Tukey’s test (p < 0.05). The results showed that E. crassipes dry matter could be used as a substrate for the germination and initial growth of corn, although the commercial agriculture substrate alone has resulted in higher initial corn growth.